Evaluation of surface changes of stainless steel miniplates and screws following retrieval from maxillofacial trauma and orthognathic surgery patients: A comparative study - Himanshu P Singh; Prerna Kataria; Ruchira Shukla; Khushboo Chhabaria Peswani; Viraj Kharkar; Shashank S Gaikwad; Ramanpal S Makkad (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: This study examines the surface changes of stainless steel miniplates and screws after their retrieval from patients who underwent maxillofacial trauma and orthognathic surgery. The assessment focuses on comparing the alterations in these materials, aiming to contribute to our understanding of their durability and performance in clinical settings. Materials and Methods: A total of 60 stainless steel miniplates and screws were collected from 30 patients who had previously undergone either maxillofacial trauma or orthognathic surgery. The retrieved miniplates and screws were carefully removed from the patients and cleaned to remove any organic debris. Each specimen was then examined for surface changes. Surface changes were evaluated using visual inspection, scanning electron microscopy (SEM), and roughness measurements. Visual inspection provided a qualitative assessment, while SEM allowed for a more detailed examination of the surfaces. Roughness measurements were conducted using a profilometer. Results: Visual inspection revealed varying degrees of surface changes in the retrieved miniplates and screws. These changes included scratches, corrosion, and discoloration. SEM analysis confirmed the presence of surface alterations, with some specimens showing more significant damage, such as pitting and cracks. Roughness measurements indicated an increase in surface roughness for both miniplates and screws, suggesting that the surfaces had become less smooth. Conclusion: This comparative study of stainless steel miniplates and screws retrieved from maxillofacial trauma and orthognathic surgery patients demonstrated that these materials undergo surface changes over time.